CSR in Sustainability Accounting: Digital Report Visualization & Transparency at PT. PLN Indonesia Power - Avrilianda, Cita Kesha (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This article aims to examine how Corporate Social Responsibility (CSR) is integrated into interactive sustainability accounting through the visualization and transparency of digital annual reports, with a focus on a case study of PT. PLN Indonesia Power. The method used in this research is a descriptive qualitative approach with documentary analysis of the company’s digitally published annual reports. This approach was chosen to evaluate how CSR elements are visualized and communicated to the public, as well as how they reflect the company’s accountability and information transparency. The key findings indicate that PT. PLN Indonesia Power has effectively adopted interactive visualization practices in presenting its CSR activities, which not only enhance the readability of information but also strengthen stakeholder trust. The implications of this research highlight the importance of digital innovation in sustainability reporting to expand public participation and corporate transparency. The novelty of this study lies in its emphasis on interactivity and digital visualization in the context of sustainability accounting, which remains underexplored in accounting literature in Indonesia.